2020
DOI: 10.1021/acssuschemeng.0c06502
|View full text |Cite
|
Sign up to set email alerts
|

Micro-particles—A Neglected but Critical Cause of Different Membrane Fouling between Aerobic and Anaerobic Membrane Bioreactors

Abstract: Until recently, membrane fouling in anaerobic membrane bioreactors (AnMBRs) was generally understood based on and by extrapolating from well-studied aerobic membrane bioreactors (AeMBRs). Clearly, this will probably be unhelpful, as each contains different microbial ecology, particles/colloids, and soluble microbial products. In this paper, a comprehensive comparison was made between these two systems to understand their different sources of foulants and, hence, differences in fouling. Our results showed that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 76 publications
(126 reference statements)
2
18
0
Order By: Relevance
“…It is indicted that the effect of PE microplastic on membrane fouling was more obvious than the microparticles in raw water. The presence of microparticles has already been shown to cause membrane fouling [38], but the pattern of membrane fouling exacerbation caused by microplastics need to be further explored. A control experiment was supplemented that the feed waters with 0.05% (w/v) sodium azide (NaN3) were used as controls variable, which can inhibit the regrowth of microorganisms (Fig.…”
Section: The Impact Of Microplastic On Permeate Water Qualitymentioning
confidence: 99%
“…It is indicted that the effect of PE microplastic on membrane fouling was more obvious than the microparticles in raw water. The presence of microparticles has already been shown to cause membrane fouling [38], but the pattern of membrane fouling exacerbation caused by microplastics need to be further explored. A control experiment was supplemented that the feed waters with 0.05% (w/v) sodium azide (NaN3) were used as controls variable, which can inhibit the regrowth of microorganisms (Fig.…”
Section: The Impact Of Microplastic On Permeate Water Qualitymentioning
confidence: 99%
“…What little information that does exist is often extrapolated from MBRs, which can vary significantly from AnMBRs. For example, a recent comparison by Yao et al [10] showed significantly more fouling in AnMBRs, significant differences in membrane fouling mechanisms, and different characteristics within extracellular polymeric substances (EPS) and soluble microbial products (SMP).…”
Section: Introductionmentioning
confidence: 99%
“…Membrane bioreactor fouling is primarily driven by EPS, which are a complex mixture of polysaccharides, proteins (structural proteins or exoenzymes), lipids/phospholipids, humic substances, and other intercellular polymers [1,10,11]. Unfortunately, the compositional, and functional details of EPS are not completely understood, while the literature has reported EPS characteristics [3,10,12]. EPS is also related to SMP, another major category of foulants.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The difference in formation of biofilm is based on microbial groups, micro-particles, and soluble microbial products, which confer potential advantages attributed to AnMBRs. Indeed, these benefits include the reduction and removal of emerging contaminants, namely, organic micropollutants (OMPs) and antibiotic resistance genes (ARGs) (Sanguanpak et al, 2019;Yao et al, 2020). Thus, a major factor not to be overlooked in membrane biofilms dynamics is the presence of inherent microbial communities in anaerobic membrane biofilms.…”
Section: Background: Anaerobic Membrane Biofilmmentioning
confidence: 99%